Function of miR-24 and miR-27 in Pediatric Patients With Idiopathic Nephrotic Syndrome - Ni, Fen-fen; Liu, Guang-lei; Jia, Shi-lei; Chen, Ran-ran; Liu, Li-bing; Li, Cheng-rong; Yang, Jun; Gao, Xiao-Jie (Frontiers in Pediatrics, 2021)
Purpose: We investigated the pathogenesis of idiopathic nephrotic syndrome (INS) by measuring the effects two specific miRNAs on Th2 cells in children with this disease. Methods: After informed consent, we enrolled 20 children with active INS before steroid initiation, 20 children with INS in remission after steroid therapy, and 20 age-matched healthy controls. Flow cytometry was used to measure the levels of Th2 cells and a cytometric bead array was used to measure the levels of IgE, interleukin (IL) -4, and IL-13. RT-PCR was used to measure the levels of miR-24 and miR-27 in CD4+TCD25− cells. PBMCs were isolated using Ficoll density gradient centrifugation, and transfected with different mimic or inhibitor miRNAs. RT-PCR was used to measure the expression of different RNAs, and flow cytometry was used to determine the percentage of Th2 cells. Results: Relative to healthy controls, children with active INS had higher percentages of Th2 cells (P<0.05), but there was no significant difference in controls and children in remission. The plasma levels of IgE, IL-4, and IL-13 were significantly increased in children with active INS (P<0.05). There were lower levels of miR-24 and miR-27 in children with active non-atopic INS (P<0.05). Transfection experiments indicated that upregulation of each miRNA decreased the percentage of Th2 cells and the level of IL-4 (P<0.05), and down-regulation of each miRNA had the opposite effects (P<0.05). Conclusion: Children with active INS, with or without atopy, had higher levels of IgE, possibly related to their higher levels of IL-13 and IL-4 due to a drift toward Th2 cells. miR-24 and miR-27 suppressed the expression of Th2 cells and have a critical function regulating Th2 cell expression in INS.